The 5 Most Pressing Ethical Issues in Biotech Medicine - SILVERMAN, ED (BioCommunications LLC, 2004)
Biotech healthcare is going through what every other emerging scientific discipline experiences – the challenge of defining its ethical boundaries. Research, costs, and privacy issues spawn concerns that third-party payers, employers, providers, and policy makers will face for years to come.